Word Formation of Indonesian and English Used by Indonesian Children in Playing Online Games - Prihandini, Asih; Muhammad, Haikal Ilya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Online games become more popular among the children since the spread of Covid virus over the world in 2019. Childs became aware of playing online games though most of the plays use English as their communication. English language, as their second language must be comprehended as well. Word formation process of Indonesian and English language color the conversation. The study aims at analyzing word formation process of Indonesian and English language used by some Indonesian children when they are playing online games. The method used in this study is a qualitative method. According to Cresswell, a qualitative method is an approach or a research to explore and understand a central phenomenon. To understand this central phenomenon, the study was done by using qualitative observation and qualitative documents. The speaking of the participants was recorded during their playing on online games and transcribed phonemically. The transcription is classified into three parts. They are morphological process in English, morphological process in Indonesian, and morphological process in English and Indonesian. After classifying the data, then it’s analyzed by using Alwi and O’Grady theories. The results show that there is morphological process constructed on their conversation during their playing such as derivational and inflectional affixes, reduplication in word class of noun, mixing code Indonesian and English. The children spontaneously and fluently combine both Indonesian and English in constructing the word. However, Indonesian language is still dominantly used and influence to the use of English one.